(untitled) (Journal of the Management Sciences, 2026)
In Sub-Saharan Africa, especially Nigeria, agriculture remains a major source of employment and rural livelihood, yet timely and affordable credit remains a serious constraint to farmers, particularly in labour-intensive enterprises such as poultry production. This study compared credit administration to poultry farmers by microfinance banks and cooperative societies in Anambra State, Nigeria. Specifically, it examined administrative practices such as interest rate, collateral requirements, processing time and loan size; compared loan application management and timeliness of disbursement; assessed farmers’ satisfaction with procedures; and identified constraints to accessing agricultural credit from both sources. A multistage sampling technique was used to select 83 poultry farmers from a sampling frame of 180 farmers trained under the World Bank Value Chain Development Initiative. Primary data were collected using structured and validated questionnaires. Data were analysed using frequency, percentages, mean and t-test. Findings showed that cooperative societies had shorter waiting periods of 8 days compared to 14 days for microfinance banks. Farmers who accessed credit from cooperatives recorded higher satisfaction with waiting time ( = 4.33), timeliness of communication ( = 4.26) and processing duration ( = 4.28). In contrast, microfinance bank beneficiaries experienced longer processing periods of over one month, higher interest rates of 25% and stricter collateral requirements. A significant difference existed between the credit administration practices of microfinance banks and cooperatives (t = 10.15; p ≤ 0.001). Cooperatives also recorded higher credit disbursement of ₦67.1 million and repayment rate of 94.5%, compared with ₦22.4 million and 76.9% for microfinance banks. The study concludes that cooperatives are more efficient in credit administration and should be strengthened to improve agricultural financing and farmers’ welfare.